2018
DOI: 10.1515/eces-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sorption Properties of Heavy Metals in Various Biosorbents

Abstract: Various techniques of determination of properties of physicochemical processes of heavy metal sorption in biosorbents were analysed. The methods of preparing and storing samples, conditions of experiment performance, as well as the methods of data interpretation were discussed. Two procedures of study were analysed: (1) in the static system of biosorbent-solution contact and (2) in the system of dynamic flow of solution.Copper cation sorption was studied. The effect of consecutive stages of the study on the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A common feature among all the adopted trials is the intimate attempts to develop the model or the ideal adsorbent. Such an adsorbent must have particular criteria such as availability at low-cost and without extensive preceding treatment, liability for regeneration, the possibility for application on a large scale, and be green or in other words does not further contaminate the environment or produce a toxic sludge [19][20][21][22][23][24]. Activated carbons are promising adsorbents, yet, being expensive and with an inability to be revitalized they confine their applications on the large scale [25].…”
Section: Introductionmentioning
confidence: 99%
“…A common feature among all the adopted trials is the intimate attempts to develop the model or the ideal adsorbent. Such an adsorbent must have particular criteria such as availability at low-cost and without extensive preceding treatment, liability for regeneration, the possibility for application on a large scale, and be green or in other words does not further contaminate the environment or produce a toxic sludge [19][20][21][22][23][24]. Activated carbons are promising adsorbents, yet, being expensive and with an inability to be revitalized they confine their applications on the large scale [25].…”
Section: Introductionmentioning
confidence: 99%
“…Once again, biosorption has appeared to be an efficacious though low-cost solution for the recovery of heavy metals. For the above reasons, sorption on materials of natural origin has become the subject of extensive studies (described, for instance, in [8][9][10][11][12][13][14][15][16][17][18][19][20][21]). The studies have demonstrated that marine algae, which are acquired at a rather low cost, have a considerable sorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir isotherms main aim is to detect the sorption capacity. However, it should be emphasized that the isotherms can also be detected in the system of different initial concentration of the solution or different absorbent mass [61]. In Langmuir isotherm, the type of isotherm can be inferred from separation factor [62].…”
Section: Adsorption Isothermsmentioning
confidence: 99%